TINJAUAN KOMPILASI HUKUM ISLAM TERHADAP PENYELESAIAN SERTIFIKAT TANAH WAKAF DI WILAYAH KANTOR KECAMATAN NOGOSARI KABUPATEN BOYOLALI TAHUN 2022-2023 - Pramudiansyah, Ilham; Wibowo, Muh. Kurniawan Budi; Pradana, Aditya Fajri Kurnia (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Waqf in Law No. 41 of 2004 is a legal act of wakif to separate and submit part of his property to be utilized forever or for a certain period of time in accordance with his interests for the purposes of worship and public welfare according to sharia. This research uses empirical qualitative research methods by collecting data through interviews, and field research and collecting primary data, the results of this research must be through the Boyolali waqf pledge certificate recording officer. The implementation of land waqf in the Nogosari Religious Affairs Office must go through a process of consultation and document preparation, appointment of nazir, examination of assets to be waqf, implementation of waqf pledges, making waqf pledge deeds, submitting waqf certificates to bpn, management by nazhr, reporting.